The future of cryptocurrencies from the perspective of Islamic economics - Harchaou, Rachida (The International tax journal, 2025)
This presentation addresses the study of the future of cryptocurrencies in the context of Islamic economics, considering the challenges and opportunities arising in this field. Having emerged in the last two decades, cryptocurrencies threaten the traditional financial system. However, there are fundamental questions regarding their compliance with Islamic economic principles, which prohibit usury (riba) and uncertainty (gharar). While cryptocurrencies offer significant opportunities to facilitate access to financing in countries with weak banking systems, the challenge lies in their high volatility and lack of compatibility with traditional banking systems. The presentation also discusses the necessity of creating Sharia-compatible legislation to ensure the safe use of cryptocurrencies. One possible approach would be to regulate cryptocurrencies by linking them to essential commodities such as gold or oil, or by issuing them through central banks. Cryptocurrencies present a dual challenge and opportunity to the Islamic economy. As these currencies evolve and Islamic financial institutions become more interested in financial technology, they are expected to play a more significant role in the Islamic financial system — provided they are adapted according to Sharia principles.